Effects of a culture-specific behavior modification program on glycated hemoglobin and blood pressure among adults with diabetes and hypertension: A randomized controlled trial. - Numsang, Patcharee; Thanasilp, Sureeporn; Thato, Ratsiri (International Journal of Nursing Sciences, 2025)
This study aimed to determine the effect of a culture-specific behavior modification program on glycated hemoglobin (HbA1c) and blood pressure among adults with diabetes and hypertension. This study was a single-blind randomized controlled trial design. From January to May 2024, a total of 60 patients with uncontrolled type 2 diabetes and hypertension from the primary care unit of a hospital in northeastern (Isan) Thailand were recruited. The intervention group received the usual care supplemented by a culture-specific behavior modification programm implemented through interactive classes and online web application consisting of information, motivation, and behavioral skills (diet, exercise, and medication use), the control group received the usual care. HbA1c and blood pressure measurements were collected at both baseline and at 12 weeks. A total of 51 patients completed the study, the intervention group (n = 26) and control group (n = 25), respectively. After 12 weeks, 23.1 % of patients in the intervention group could maintain their HbA1c < 7.0 %; those with poorly controlled HbA1c decreased from 7.7 % at baseline to 3.8 % at 12 weeks. After 12 weeks, 69.2 % of intervention group participants could maintain systolic blood pressure <130 mmHg and 53.8 % could keep diastolic blood pressure <80 mmHg. Analysis revealed that HbA1c, systolic and diastolic blood pressure levels in the intervention group were lower than the control group after the intervention (P < 0.05). There was a statistically significant difference a linear combination of HbA1c and blood pressure (systolic and diastolic BP levels) between time and group (P < 0.05). These results suggest that healthcare providers can incorporate elements of this program to manage blood glucose and blood pressure effectively. Future studies should consider a longitudinal design with a larger sample size and include outcomes of lipid levels to confirm long-term motivation.